Normal contact simulation of non-Gaussian fractal surfaces - Hauer, Franz; Willner, Kai (Proceedings of the 81st Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2010)
Friction forces between contact partners in dry friction are primarily caused by adhesion and ploughing. In adhesive contact, tangential loads are transferred by shear forces within the real contact area. The real contact area is usually smaller than the apparent contact area, because real surfaces are always rough and only the highest surface peaks are in contact for moderate loads. Thus the size of the real contact area is a suitable measurement for the behaviour in dry friction. The normal contact is simulated with a halfspace model. The contact surfaces are modelled numerically in order to enable the independent investigation of the influence of several surface properties, namely the fractal behaviour on small scales, non-Gaussian height distribution and anisotropy. Fractal behaviour means that asperities are covered with smaller asperities of the same shape. Surface anisotropy means that valleys and ridges are oriented in a certain direction.
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-TM.normal_8